Musealizing Archaeological Sites. Considerations on Research, Conservation, and Dissemination: A Case Study from the Gavà Mines Archaeological Park. (3rd April 2015) - Panosa, Maria Isabel
Abstract : This paper offers some considerations on the concept of musealization at archaeological parks. It focuses on aspects of the design and development of a musealized archaeological site: conservation, security, museological techniques, communication, and, above all, the role of research as the basis to develop continuously renewed and high-quality content for public dissemination. The case of the Gavà Mines Archaeological Park (Barcelona, Catalonia, Spain) is used to exemplify the reflections presented in this article.